Fulfillment of The Right to Education in the Border Area of West Kalimantan through a Legal Harmonization Integrative Model Based on Social Reality - Endah Rantau Itasari; Ervin Riandy; Evi Purwanti; Etra Arbas; Yudith Evametha Vitranilla (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
The fulfillment of the right to education is a constitutional obligation and a state commitment stipulated in various international legal instruments, including international human rights principles that recognize education as a fundamental right of every individual. This principle guarantees equal access to and quality education without discrimination, including for communities living in border areas. This study aims to find out the actual conditions of the fulfillment of the right to education in the Aruk, Jagoi Babang and Entikong borders, as well as to develop and introduce a Legal Harmonization Integrative Model Based on Social Reality and International Human Rights Principles as a conceptual framework to connect formal legal norms with the social dynamics of border communities. Thus, education policies can be formulated in a more adaptive, participatory, contextual, and human rights perspective. The research approach uses empirical legal methods with a juridical-sociological approach through surveys, in-depth interviews, and participant observation. The results show that the reality on the ground of the border areas of West Kalimantan still face significant disparities due to limited infrastructure, a shortage of educators, and policies that are not fully aligned with local social, economic, and cultural conditions. The development of this model has received support from various parties in the West Kalimantan border region because it may strengthen the relationship between the legal framework and the actual needs of the community, create education policies that are responsive to the local context, and encourage the achievement of educational equity